Authorial Pronoun We - Lely Tri Wijayanti; Nur Indah Sholikhati; Exwan Andriyan Verrysaputro (J-Lalite: Journal of English Studies, 2022)
This study aims to decipher the use of authorial pronoun we as a politeness strategy in the EFL academic writing. The data consist of 56 published research articles taken from the Corpus of State University of Malang Indonesian Learners’ English. The articles were written by Indonesian undergraduate students co-authored with their thesis supervisors. Attempting to categorize pronoun we into inclusive, exclusive, and ambiguous types in the co-authored texts, we identify seven functions of the authorial pronoun. The result unveils that the ambiguous authorial pronoun we appear to be the most frequently used politeness device to minimize face threatening acts (FTA).